2015
DOI: 10.1002/adma.201501214
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro‐Substituted n‐Type Conjugated Polymers for Additive‐Free All‐Polymer Bulk Heterojunction Solar Cells with High Power Conversion Efficiency of 6.71%

Abstract: Fluorinated n-type conjugated polymers are used as efficient electron acceptor to demonstrate high-performance all-polymer solar cells. The exciton generation, dissociation, and charge-transporting properties of blend films are improved by using these fluorinated n-type polymers to result in enhanced photocurrent and suppressed charge recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
328
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(336 citation statements)
references
References 51 publications
6
328
1
1
Order By: Relevance
“…The trend observed systematically for such polymers is a lowering of their HOMO when compared to their non-fluorinated analogues. The lowering of the HOMO is of Recently, Jo and co-workers applied the fluorination strategy to one of the most investigated n-type copolymers, the P(NDI2OD-T2) derivative (Figure 21) [95]. Amazingly, in their specific case, the authors observed, by cyclic voltammetry, a raising LUMO level upon backbone fluorination of about 0.15 eV ( Table 6).…”
Section: Discussionmentioning
confidence: 98%
“…The trend observed systematically for such polymers is a lowering of their HOMO when compared to their non-fluorinated analogues. The lowering of the HOMO is of Recently, Jo and co-workers applied the fluorination strategy to one of the most investigated n-type copolymers, the P(NDI2OD-T2) derivative (Figure 21) [95]. Amazingly, in their specific case, the authors observed, by cyclic voltammetry, a raising LUMO level upon backbone fluorination of about 0.15 eV ( Table 6).…”
Section: Discussionmentioning
confidence: 98%
“…Since most good OSCs that are used as n-type materials like [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) and N2200 have a lowest unoccupied molecular orbital (LUMO) around −4.0 eV, [7,8] it is very difficult to realize a stable dopant with a HOMO above −4.0 eV as would be required for efficient electron transfer. Fortunately, Wei et al have reported a promising material, (4-(1,3-dimethyl-2,3-dihydro-1H-benzoimidazol-2-yl)phenyl) dimethylamine (N-DMBI), that can be used as stable n-type dopant due to a two-step thermally activated doping mechanism.…”
mentioning
confidence: 99%
“…25 From Fig. 3(b), we determined the exponential factor (a) for the devices processed with 0%, 3%, 5%, and 8% DIO as 0.91 6 0.01, 0.92 6 0.01, 0.96 6 0.02, and 0.87 6 0.01, respectively.…”
Section: -2mentioning
confidence: 99%